Effects of various conditions on and empirical modeling of baking process in convection oven - Mohamad Shahapuzi, Nur Syafikah (2015)
The presence of airflow during heating process is expected to increase the heat uniformity in a closed heating chamber. The circulation of hot air in convective oven has overcome the static and dominant radiant heat that occurs in conventional oven. The objectives of this study are to investigate the effect of airflow and setting temperature on oven and cake temperatures, and final cake qualities for convectional and modified oven, and to develop an empirical model, simulate and control the oven temperature during baking. Experimental studies were conducted in convective oven (0 m/s=0% for without airflow and 1.88 m/s=100% for with airflow condition) and in modified convective oven within different airflow velocity (0 m/s=0%, 0.95 m/s=50%, 1.43 m/s=75% and 1.88 m/s=100%), setting temperature (low=160°C, medium=170°C and high=180°C) and type of controller (On-off and Proportional-integral-derivative, PID). During baking, oven and cake temperatures were measured simultaneously whereas cake expansion, weight loss and air humidity were measured periodically. Measurement of final quality includes volume, moisture content, surface colour and texture. Step tests were conducted during baking by changing the setting temperature from 150°C to 190°C. MATLAB R2013a was used to identify the model that relates the oven temperature at hot air exit stream to the setting temperature. The process model is represented as First Order Plus Time Delay (FOPTD) model and the SIMULINK was used for model and tuning verification. Lambda method was used as the tuning method. The presence of airflow increased the heating rate by 3 times and maintained the oven temperature near to the setting temperature. With the presence of airflow in the convectional oven, the oscillation reduced from 12.98 - 30.27% to 3.17 - 4.02%. Significant reduction in heating time, overshoot and fluctuation were seen in the modified convective oven. The presence of airflow in the modified convective oven showed a significant effect during second stage of baking with 12%, increase of internal cake heating rate and the relative height increased up to 110% than its initial height. The increase of setting temperature and airflow velocity resulted in larger cake volume, moister crumb layer but drier top crust layer. The firmness was reduced but springiness increased. Cake baked with the presence of airflow are more porous in crumb texture, intense browning surface colour (ΔE = 32.28 - 36.79) and acceptable moisture content (25-28%). The developed closed-loop model had an excellent agreement with the experimental data (R2>0.9) and the maximum errors was less than ±2%. The process model parameters are Kp=0.1, τp=10.91 s and τd=4.74 s. The new Modified Lambda method obtained satisfactory performance in terms of overshoot, response time and settling time. The simulation result showed the new controller setting (controller gain, KC=11.70 and integral gain, KI=0.092) gave good performance to the set point change. Uniform heat in the oven is needed to have better product qualities. The presence of airflow, sophisticated controller and appropriate tuning is useful to attain uniform heating.